Preparations and applications of zinc oxide based photocatalytic materials - Sun, Yue; Zhang, Wei; Li, Qun; Liu, Huijie; Wang, Xiaolei (Advanced Sensor and Energy Materials, 2023)
Among the semiconductor photocatalytic materials, zinc oxide (ZnO)-based composites show promising research prospects in the field of environmental and biomedical materials due to their simple preparation, low cost, high photocatalytic performance, excellent physical stability and biocompatibility. Therefore, this review summarizes the preparation and application of ZnO-based composites with high catalytic performance. Firstly, the modification strategies of ZnO by researchers in recent years are reviewed, including non-metal doping, metal doping, noble metal deposition, compounding with semiconductors and other surface modification methods. Subsequently, the applications of photocatalytic ZnO-based composites in biomedicine (antibacterial, anticancer, biosensing, etc.), environmental pollution and other fields in the last five years are presented. Finally, the challenges faced by the future development of ZnO-based composites in various fields are discussed. We hope that this review will provide ideas for the design and development of efficient photocatalysts based on ZnO-based composites in further applications.